Design and development of highly efficient nano fluidic flat plate solar collector - Farhana, Kaniz (2019)
The increase in demand for energy along with the depletion of conventional energy sources requires the improved utilization of renewable energy resources. Moreover, the unfavourable response of existing energy urges to take necessary action rapidly. Therefore, it is desired to generate an alternative source of energy or renewable energy for the industries. Among all renewable energy resources, solar energy is the most advantageous alternative to conventional energy sources owing to its inexhaustibility and green property. Generally, solar energy is harvested using different solar collectors. Solar collectors are devices that convert solar radiation into heat or electricity. However, the efficiency of the solar collector specifically flat plate solar collector is still not adequate. Thus, to form an optimum designed of a flat plate solar collector and by reintroducing the working fluid with the new transport medium; the efficiency of the collector can be improved. The competent step to enhance the efficiency of the solar collector is to redesign the flat plate solar collector considering the number and diameter of the header and riser tubes of flat plate solar collector. Secondly, replacing the working fluid inside the header and riser tubes with ethylene glycol-based Al2O3 and CNC nanofluids flowing through them. And finally, analysing the thermal performance of these new transport mediums in flat plate solar collector. This study is carried out in different phases viz. computational numerical simulations to design flat plate solar collector; measurement and evaluation of distinctive thermo-physical properties of Al2O3 and CNC nanofluids including stability, thermal conductivity, viscosity, specific heat, density and pH; implementation of nanofluids in the solar collector and finally, numerical simulation based on the experimental design and experimental properties of nanofluids. Experiment executed with a fixed flow rate and in the steady-state condition under solar irradiation. In results, the optimum 8-23-12 (number of riser tubes-diameter of header-diameter of riser) design of header and riser tubes of solar collector selected based on the statistical analysis of numerical simulations. From the thermo-physical point of view, thermal conductivity increased in a maximum of 13.4% and 11.5% for Al2O3 and CNC nanofluids respectively. Furthermore, the highest of 36% and 19% viscosity obtained with the augmentation of Al2O3 and CNC nanoparticle into the base fluid at 30oC temperature respectively but decreased with the raising of temperature. Moreover, decrement of specific heat occurred due to an increment of volume concentrations of nanofluids. However, specific heat capacity enhanced by the progressive gradient of temperature. On the other hand, contraction of the density of nanofluids obtained with an improvement of temperature and of 3.8% decreased in maximum at 80oC temperature. Al2O3 nanofluids showed the pH range of 2 to 4 and CNC nanofluids were within 5 to 7.5 scale of pH. The experimental study has implied that up to 2.48% and 8.46% efficiency of solar collector enhanced by using 0.5% Al2O3 and 0.5% CNC nanofluids respectively. And the most significant result is that of about 5.8% efficiency can be improved in flat plate solar collector by CNC/water-EG nanofluid. In addition, all types of nanofluids performed better convection heat transfer and quick heat diffusion characteristics with laminar fluid flow behaviour. Applying CNC/water-EG nanofluid enhances the efficiency of a flat-plate solar collector to consume the limitless solar energy to create an alternative source of energy for the industries.